A Novel Laser Energy Ablation Catheter for Endocardial Cavo-Tricuspid Isthmus Ablation and Epicardial Ventricular Lesion Formation: An in vivo Proof-of-Concept Study - Krist, Dennis; Linz, Dominik; Schotten, Ulrich; Zeemering, Stef; Leenen, Dwayne (Frontiers in Medical Technology, 2022)
Aim This proof-of-concept study aimed to investigate atrial and ventricular lesion formation by a 20-mm linear laser ablation catheter, regarding lesion depth and tissue damage. Methods In total, 6 female swines underwent standard femoral vein access to introduce a novel 20-mm linear laser ablation catheter in the right atrium to perform endocardial cavotricuspid isthmus (CTI) ablations. The navigation took place under fluoroscopy with additional visualization by intracardiac echocardiograph. Via a sternotomy, epicardial ablations were performed on the surface of the left ventricle (LV), right ventricle (RV), and right atrial appendage (RAA). Procedural safety was assessed by registration of intraprocedural adverse events and by macroscopic examination of the excised hearts for the presence of charring or tissue disruption at the lesion site. Results Altogether 39 lesions were created, including 8 endocardial CTI (mean lesion length 20.6 ± 1.65 mm), 26 epicardial ventricle (mean lesion length LV: 25.3 ± 1.35 mm, RV: 24.9 ± 2.40 mm), and 5 epicardial appendage ablations (mean lesion length RAA: 26.0 ± 3.16 mm). Transmurality was achieved in all CTI and atrial appendage ablations, in 62% of the RV ablations and in none of the LV ablations. No perforation or steam pop occurred, and no animal died during the procedure. Conclusion In this porcine study, the 20-mm linear laser ablation catheter has shown excellent results for endocardial cavotricuspid isthmus ablation, and it resulted in acceptable lesion depth during atrial and ventricular epicardial ablation. The absence of tissue charring, steam pops, or microbubbles under the experimental conditions suggests a high degree of procedural safety.